Bill C-31: Limited Access to Refugee Determination and Protection - Bossin, Michael (Refuge: Canada’s Journal on Refugees, 2001)
This article deals with the effect of the proposed Immigration and Refugee Protection Act (Bill C-31) on access to Canada’s refugee determination system and its pre-removal risk-assessment procedures. The author examines public statements about government plans for increased overseas interdiction of refugee claimants, provisions that expand the definition of persons ineligible to have their claims heard by the Immigration and Refugee Board (particularly those concerning “serious criminality”), and the proposed new system for pre-removal risk assessment. His conclusion is that, should these proposals come into effect, fewer people will have access to refugee and other protection in Canada.